Development of an information system for cycling navigation - Matos, Francisco Lé de (2021)
This study develops an information system for cycling navigation based on seven different bikeability indicators: travel time, energy expenditure, effort distribution, infrastructure performance, safety, comfort and emission hotspots. Therefore, field data were collected in a selected cycling network map of Aveiro, Portugal, during the weekdays' afternoon peak hour period. A conventional aluminum bicycle equipped with a GNSS data logger, a wireless heart rate recorder device and a video camera were used. Using the defined methodologies as well as GPS Visualizer and ArcGIS, a total of 8 hours of video and approximately 100.000 second by second data points were analyzed and organized through a 449-link map. Through three case studies, several optimal solutions for different OD pairs were studied using Dijkstra's shortest path algorithm. Results show significant tradeoffs between the traced routes according to the chosen type of indicator, pointing the information system' utility in providing useful information to cyclists and support management systems.